Drag reducer for compact shale oil reservoir and slickwater fracturing fluid system containing drag reducer
By using graphene hybrid hyperbranched polymers and modified nanosilicon dioxide in slippery water, the problem of slow swelling and easy adsorption of resistance reducers in existing slippery water is solved, and the effects of rapid swelling and low damage are achieved, which significantly improves the recovery rate of shale reservoirs.
Patent Information
- Application Number
- CN202311433953.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The resistance reducing agent in existing slippery water swells slowly in shale reservoirs and is easily adsorbed on the rock surface, resulting in blockage of pore throat and affecting the fracturing effect.
Graphene hybrid hyperbranched polymer is used as a drag reducing agent, and combined with anionic surfactant and modified nanosilicon dioxide, to improve the adsorption of polymer molecular chains on the shale surface, reduce interfacial tension, and improve recovery.
The rapid swelling and low damage characteristics of slippery water in shale reservoirs are achieved, which significantly improves recovery rates and reduces reservoir penetration damage.
Smart Images

Figure CN119912933A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas field fracturing, and relates to a drag reducer for a dense shale oil reservoir and a slick water fracturing fluid system containing the drag reducer. Background Art
[0002] With the increasing demand for oil and gas resources and the continuous reduction of conventional oil and gas resources, the exploration and development of shale oil resources are of great significance to the country's search for alternative energy and energy security. Although shale oil resources are huge, shale oil reservoirs have the characteristics of low porosity and permeability, complex pore structure, and strong microscopic heterogeneity; in addition, the natural energy of shale oil is very low and has no industrial mining value, so reservoir transformation is generally required.
[0003] In the process of shale oil development, large-volume and large-liquid volume fracturing is a key technology. Slick water is a key part of volume fracturing, but the drag reducer commonly used in slick water is a linear polyacrylamide with a molecular weight of about 5 million. In addition to its slow swelling rate, the hydrophilic groups on the molecular chain of this drag reducer are easily adsorbed on the rock surface of shale, and finally form agglomerates, blocking the tiny pores of shale, seriously affecting the effect after fracturing.
[0004] Chinese invention patents CN104559997B and CN104559998B respectively disclose slippery water for shale gas fracturing, which is composed of drag reducing agents with different molecular weights and different intrinsic viscosities, clay stabilizers, drainage aids, potassium chloride fungicides and residual water. The drag reducing agent is an acrylamide copolymer obtained by copolymerizing acrylamide as the main structural unit, ionic structural units and functional monomers. The additives used in the slippery water of this system have a fast dissolution rate and are evenly dispersed, which can meet the technical requirements of high-displacement and large-liquid fracturing construction in shale gas reservoirs.
[0005] Chinese invention patent CN108865105B discloses a slippery water system with low adsorption damage. The slippery water system uses linear polyacrylamide with a molecular weight of 5-8 million as a drag reducer and an anionic fluorocarbon surfactant as a drainage aid. The adsorption amount of polyacrylamide in the slippery water on the shale rock surface is significantly reduced, thereby improving the production increase effect after fracturing. After adding the adsorbent to the slippery water formula system, the cost increase is less than 10%, and the construction process remains unchanged.
[0006] Chinese invention patent CN112694885B discloses a highly active drag reducer, a self-infiltration and energy-enhancing type slippery water fracturing fluid system suitable for shale oil reservoirs, and its preparation method and application. Hydrophobic and hydrophilic groups are simultaneously introduced into the polymer structure to obtain a macromolecular polymer, and then a high-molecular polymer prepared by introducing a highly active surfactant is used as a highly active drag reducer to prepare a self-infiltration and energy-enhancing type slippery water fracturing fluid. During the fracturing operation, the slippery water fracturing fluid can infiltrate into the shale matrix to drive crude oil into cracks or large pores. At the same time, the fracturing fluid does not flow back, but is retained in the shale matrix to increase formation energy and improve the shale oil recovery rate. It not only solves the current problem of difficult flowback of fracturing fluid, but also achieves a good oil displacement effect, and has important practical value.
[0007] The current drag reducing agent used in slick water has a relatively simple composition, and usually only considers the effects of fracturing and flowback. How to use slick water to improve recovery and reduce reservoir permeability damage is also not to be ignored. Therefore, it is of great research significance to develop a slick water fracturing fluid that combines fracturing, flowback, low permeability damage and can effectively improve recovery through the optimization and improvement of drag reducing agents. Summary of the invention
[0008] In view of the problems existing in the prior art, the present invention provides a drag reducer for tight shale oil reservoirs and a slick water fracturing fluid system containing the same. A hyperbranched polymer is used as the drag reducer, which exhibits rapid swelling and low damage to shale pores when used in the slick water fracturing fluid system. Meanwhile, an anionic surfactant is used as a drainage aid and modified nano-silica is used as an auxiliary additive, which can effectively improve the adsorption of polymer molecular chains on the shale surface, reduce interfacial tension, and improve the recovery rate.
[0009] The present invention provides a dense shale oil reservoir drag reducer, wherein the drag reducer is a graphene hybrid hyperbranched polymer, and the structure is represented as follows:
[0010]
[0011] Where n represents the number of branch chains A;
[0012] The structure of the branched chain A is:
[0013]
[0014] In the formula, x:y:z=70-80:15-25:1-5.
[0015] Furthermore, the viscosity average molecular weight of the hyperbranched polymer is 1-3 million.
[0016] The present invention also provides application of the drag reducer in slippery water.
[0017] The present invention also provides slippery water, which comprises: a drag reducer, a drainage aid, an anti-swelling agent, an auxiliary additive and water; the drag reducer is any of the above-mentioned hyperbranched polymers.
[0018] Furthermore, the composition of the slippery water includes, by mass percentage, 0.05-0.1% of a drag reducer, 0.1-0.3% of a drainage aid, 0.1-0.3% of an anti-swelling agent, 0.1-0.5% of an auxiliary additive and the balance of water.
[0019] Furthermore, the drainage aid is an anionic surfactant, selected from at least one of sodium secondary alkyl sulfonate, sodium dodecyl alcohol polyoxyethylene ether sulfonate and sodium dodecyl alcohol polyoxyethylene ether carboxylate.
[0020] Furthermore, the polymerization degree of the polyoxyethylene ether in the sodium dodecyl alcohol polyoxyethylene ether sulfonate and sodium dodecyl alcohol polyoxyethylene ether carboxylate is 8-40.
[0021] Furthermore, the anti-swelling agent is at least one of potassium chloride, cationic quaternary ammonium salt and polyquaternary sulfate polymer.
[0022] Furthermore, the auxiliary additive is modified nano-silicon dioxide.
[0023] Furthermore, the modified nano-silica is obtained by modifying nano-silica with γ-aminopropyltriethoxysilane.
[0024] The present invention also provides a method for preparing the above-mentioned slippery water, which specifically comprises the following steps:
[0025] (1) adding any of the above-mentioned hyperbranched polymers into water and stirring to obtain a polymer solution;
[0026] (2) Add anti-swelling agent, drainage aid and auxiliary additives to the above polymer solution and continue stirring to obtain the product.
[0027] Furthermore, in step (1) and step (2), the stirring temperature is room temperature and the stirring time is 30-60 min.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The low molecular weight hyperbranched polymer of the present invention is used as a drag reducing agent in slippery water and has the characteristic of rapid swelling;
[0030] (2) The hyperbranched structure gives the polymer a larger molecular size and also helps to slow down the entry of the polymer molecular weight into the shale pores and damage the matrix;
[0031] (3) The present invention uses anionic surfactants as drainage aids to improve the wettability of the reservoir, allowing the modified nano-silica to be adsorbed on the shale surface, further slowing down the adsorption of polymer molecular chains on the shale surface, and at the same time significantly reducing the oil-water interfacial tension, thereby replacing the crude oil in the matrix through imbibition. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The results of improving wettability of the slick water fracturing fluid system in Example 1;
[0033] Figure 2 This is the imbibition effect of the slick water fracturing fluid system under different crude oil viscosities in Example 1;
[0034] Figure 3 This is the conductivity curve of the polymer dissolution process of the slick water fracturing fluid system in Example 1. DETAILED DESCRIPTION
[0035] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0036] The conventional guar gum solution used in Comparative Example 1 of the present invention was purchased from Shaanxi Senrui Petroleum Technology Development Co., Ltd.
[0037] Embodiment 1:
[0038] 1. Preparation of graphene hybrid hyperbranched polymer core:
[0039] (1) 2 g of graphene oxide was added to 50 mL of toluene, and ultrasonicated for 30 min. 0.8 g of γ-aminopropyltriethoxysilane was added dropwise under a nitrogen atmosphere, and then the temperature was raised to 80 °C for reaction. After 24 h, high-speed centrifugation and methanol / n-hexane (v / v, 1 / 1) were repeatedly washed for 5 times, high-speed centrifugation, and vacuum dried at 60 °C to obtain modified graphene oxide, MGO;
[0040] (2) 1.0 g of MGO was added to 100 mL of methanol and dispersed by ultrasonic oscillation for 30 min. Then, it was placed in an ice-salt bath and 10 mL of a methanol mixed solution of maleic anhydride (the dissolved mass of maleic anhydride in the mixed solution was 1.0 g) was added dropwise under a nitrogen atmosphere. Then, the mixed solution was heated to 25°C and reacted for 48 h. The mixed solution was washed five times by high-speed centrifugation and methanol / n-hexane mixed solution (v / v, 7 / 3), high-speed centrifugation, and vacuum drying at 60°C to obtain the added modified graphene oxide, MGO-1.
[0041] (3) 1.0 g of MGO-1 was added to 100 mL of methanol, and then placed in an ice-salt bath pot, and 10 mL of ethylenediamine / methanol mixed solution (the dissolved mass of ethylenediamine in the mixed solution was 1.5 g) was added dropwise; then, the mixed solution was heated to 25°C and reacted for 48 h; high-speed centrifugation and methanol / n-hexane mixed solution (v / v, 7 / 3) were repeated for 5 times, and amidated modified graphene oxide, MGO-2, was obtained by high-speed centrifugation and vacuum drying at 60°C;
[0042] (4) repeating steps (2) and (3) to obtain hyperbranched graphene oxide;
[0043] (5) 1.0 g of hyperbranched graphene oxide was dispersed in 20 mL of dimethyl sulfoxide, ultrasonicated for 30 min, then placed in an ice-salt bath, and 20 mL of a mixed solution of maleic anhydride and dimethyl sulfoxide (the mass of dimethyl sulfoxide was 0.5 g) was added dropwise under a nitrogen atmosphere, and then the temperature was raised to 65 °C for 12 h; high-speed centrifugation and methanol / n-hexane (v / v, 7 / 3) were repeated for 5 times, and high-speed centrifugation and vacuum drying at 60 °C were performed to obtain a graphene hybrid hyperbranched polymer core AB n .
[0044] 2. Preparation of hyperbranched polymers:
[0045] (1) Add acrylamide (30 g), acrylic acid (5 g), and triphenylethylphenol polyoxyethylene ether methacrylate (6 g) into deionized water, adjust the pH value of the system to 7 with sodium hydroxide solution, and control the total mass concentration of the monomers to be maintained at 30%;
[0046] (2) nitrogen was then introduced into the system for 30 minutes to remove oxygen in the system, and ammonium persulfate, sodium bisulfite and azobisisobutyronitrile hydrochloride were added into the system in sequence under continuous stirring (wherein the mass ratio of ammonium persulfate, sodium bisulfite and azobisisobutyronitrile hydrochloride was 1:1:1.5, and the total amount of initiator added was 0.2% of the mass of the monomer); nitrogen was introduced into the system again until the system began to become viscous;
[0047] (3) The mixture is then allowed to react for 7 hours. After the reaction is completed, a hyperbranched polymer is obtained by granulation, drying and crushing.
[0048] Embodiment 2:
[0049] Add 99.4 g of water to a small mixing tank, add 0.1 g of a hyperbranched polymer (molecular weight 3 million) under stirring, add 0.2 g of potassium chloride, 0.2 g of sodium secondary alkyl sulfonate and 0.1 g of γ-aminopropyltriethoxysilane-modified nano-silica after stirring for 30 minutes, and stir for 30 minutes to obtain a slick water fracturing fluid system.
[0050] The results of slick water viscosity and interfacial tension between slick water and crude oil are shown in Table 1;
[0051] The results of improving the wettability of oil-wet rock slices are as follows: Figure 1 As shown;
[0052] The dynamic imbibition results in fracture core (permeability, 0.0287 mD) under different crude oil viscosities are shown in Figure 2. Figure 2 shown.
[0053] Embodiment 3:
[0054] Add 99.3g of water to a small mixing tank, add 0.2g of hyperbranched polymer (molecular weight 1 million) under stirring, stir for 30 minutes, add 0.2g of polyquaternary sulfate polymer (fatty acid polyoxyethylene ether ammonium sulfate), 0.2g of sodium dodecyl alcohol polyoxyethylene ether sulfonate (polyoxyethylene ether polymerization degree 20) and 0.1g of γ-aminopropyltriethoxysilane-modified nano-silica, stir for 30 minutes to obtain a slick water fracturing fluid system.
[0055] Embodiment 4:
[0056] Add 98.8g of water to a small mixing tank, add 0.1g of hyperbranched polymer (molecular weight 3 million) under stirring, stir for 30 minutes, add 0.3g of cationic polyquaternary ammonium polymer (polyDDA), 0.3g of sodium dodecyl alcohol polyoxyethylene ether carboxylate (polyoxyethylene ether polymerization degree 20) and 0.5g of γ-aminopropyltriethoxysilane-modified nano-silica, stir for 30 minutes to obtain a slick water fracturing fluid system.
[0057] Slippery water performance test:
[0058] Viscosity test: The viscosity of the slickwater fracturing fluid system was measured using a high-temperature and high-pressure Hake rheometer. Test conditions: test temperature 90°C, shear rate 170s -1 ;
[0059] Surface tension test: The ability of the slickwater fracturing fluid system to reduce the oil-water interfacial tension is measured using a high-temperature and high-pressure shape analyzer; test conditions: temperature 90°C;
[0060] Swelling rate test: The solubility of the polymer is determined using the conductivity method;
[0061] Table 1 Test results of various properties of slick water
[0062]
[0063]
[0064] It can be seen from the above table that the slickwater fracturing fluid system of the present invention can reverse the wettability of oil-wet rock slices to hydrophilicity; after the slickwater fracturing fluid system of the present invention is injected and the well is kept for 3 days, the dynamic imbibition of slickwater can increase the recovery rate by more than 20%.
[0065] The permeability of the core was measured through core flooding experiments, and the permeability damage rate was calculated. The results are shown in Table 2;
[0066] Table 2 Permeability damage rate results of the slick water fracturing fluid system of the present invention and conventional guar gum fluid
[0067] Slippery Water Initial permeability (mD) Permeability after pollution (mD) Penetration damage rate (%) Example 1 0.041 0.039 4.9 Conventional guar gum solution 0.052 0.032 38.4
[0068] It can be seen from the above table that the slick water fracturing fluid system prepared by the present invention gives the polymer a larger molecular size due to the hyperbranched structure, which also helps to slow down the polymer molecular weight from entering the shale pores to damage the matrix, and greatly reduces the damage rate to the shale pores.
[0069] In summary, the slick water fracturing fluid system prepared by the present invention has excellent comprehensive performances such as fracturing, flowback, low permeability damage and high recovery rate, and is widely used in shale oil reservoir fracturing and exploitation.
[0070] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A tight shale oil reservoir drag reducer, characterized in that: The drag reducer is a graphene hybrid hyperbranched polymer, and the structure is represented as follows: Where n represents the number of branch chains A; The structure of the branched chain A is: In the formula, x:y:z=70-80:15-25:1-5.
2. The drag reducing agent according to claim 1, characterized in that The viscosity average molecular weight of the hyperbranched polymer is 1-3 million.
3. Use of the drag reducer according to any one of claims 1-2 in slippery water.
4. A slippery water, characterized in that: The slippery water composition comprises: a drag reducer, a drainage aid, an anti-swelling agent, an auxiliary additive and water; the drag reducer is the hyperbranched polymer described in any one of claims 1-2.
5. The slippery water according to claim 4, characterized in that: The composition includes, by mass percentage, 0.05-0.1% of a drag reducer, 0.1-0.3% of a drainage aid, 0.1-0.3% of an anti-swelling agent, 0.1-0.5% of an auxiliary additive and the balance of water.
6. The slippery water according to claim 4, characterized in that: The drainage aid is an anionic surfactant selected from at least one of sodium secondary alkyl sulfonate, sodium dodecyl alcohol polyoxyethylene ether sulfonate and sodium dodecyl alcohol polyoxyethylene ether carboxylate; The anti-swelling agent is at least one of potassium chloride, cationic quaternary ammonium salt and polyquaternary sulfate polymer; The auxiliary additive is modified nano silicon dioxide.
7. The slippery water according to claim 6, characterized in that: The polymerization degree of the polyoxyethylene ether in the sodium dodecyl alcohol polyoxyethylene ether sulfonate and sodium dodecyl alcohol polyoxyethylene ether carboxylate is 8-40.
8. The slippery water according to claim 6, characterized in that: The modified nano silicon dioxide is obtained by modifying the nano silicon dioxide with gamma-aminopropyltriethoxysilane.
9. The method for preparing slippery water according to any one of claims 4 to 8, characterized in that: The following steps are involved: (1) adding the hyperbranched polymer according to any one of claims 1 to 2 into water, and stirring to obtain a polymer solution; (2) Add an anti-swelling agent, a drainage aid and auxiliary additives to the above polymer solution and continue stirring to obtain the product.
10. The preparation method according to claim 9, characterized in that: In step (1) and step (2), the stirring temperature is room temperature and the stirring time is 30-60 min.
Citation Information
Patent Citations
A kind of slick water for shale gas fracturing and preparation method thereof
CN104559997B
A kind of slick water for shale gas fracturing and preparation method thereof
CN104559998B
A low-adsorption, harmful slippery water system
CN108865105B
Highly active drag reducers, self-permeable slickwater fracturing fluid systems suitable for shale oil reservoirs, their preparation methods and applications
CN112694885B